Development of a Self-Care Model for Diabetic Patients with Uncontrolled Blood Sugar Levels in Sam Tumbon Community Medical Center, Songkhla Province - Rukchuchuen, Yupha; Nawsuwan, Kittiporn (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Self-care to control blood sugar levels is crucial for preventing or delaying complications of diabetes. Patients need knowledge and support from an interdisciplinary team to adjust their behavior and control their blood sugar levels. This research aimed to study the current situation, develop a model, and examine its effectiveness. Methods The research and development was conducted in three phases: 1) document analysis and qualitative methods (R1), 2) model draft development (D1), and 3) effectiveness study (R2). A quasi-experimental design with two groups, pre- and post-measurement, was used. The sample consisted of 44 diabetic patients with uncontrolled blood sugar levels per group. The instruments used were the ATPH 3T Model, a self-care behavior questionnaire, and HbA1c measurements. The content validity index values ranged from .67 to 1.00, and the Cronbach’s alpha reliability was 0.857. Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests. Results 1) There was an increase in the number of diabetic patients with uncontrolled blood sugar levels, but the number of blood tests has decreased. These patients have problems with diet, exercise, medication adherence, and complications. They required knowledge and monitoring. 2) The ATPH 3T Model consisted of Assessment (A), Transitional (T), Productive (P), and Healthcare Monitoring and Support (H). 3) The experimental group following the ATPH 3T Model showed a statistically significant increase in self-care behavior scores and a decrease in HbA1c levels (p < .001, .001), which was significantly better than the control group (p = .049, <.001). Conclusion and Recommendations The ATPH 3T Model is effective in promoting self-care behaviors and reducing HbA1c levels. This model should be used to continuously organize activities.